Reformasi Birokrasi Pelayanan Publik Di Polres Solok Kota - Bobi Rizki Ananda; Roni Ekha Putera; Ria Ariany (Institut Ilmu Sosial dan Manajemen STIAMI, 2019)
Decree of the Minister of State Apparatus Empowerment and Bureaucratic Reform (KEPMEMPAN and RB) Number 10 of 2019 concerning the Establishment of Public Service Provider Units at Ministries and Institutions as the Location of Public Service Evaluation in 2019. It is said that there are 54 institutions / agencies which are locations for evaluating public services, from The 54 institutions / ministries of West Sumatra Province became one of the evaluation institutions in public services by the Ministry of Empowerment of the State Apparatus and Bureaucratic Reform, the institution which became a place for evaluating public services in West Sumatra was the Indonesian National Police. This study aims to describe and analyze what has been done by the Solok City Police Station in achieving good governance through bureaucratic reform. This research is motivated by Solok Kota Police to be the only institution in West Sumatra that has succeeded in carrying out reforms. This study uses qualitative research methods, data sources in the form of primary and secondary data. Primary data were obtained from interviews and observations, while secondary data were obtained from documentation. The results showed that the Solok Kota Police had succeeded in carrying out Bureaucratic Reform in the field of Public Services, this was proven by the Solok City Police receiving an award by Kemempan RB as the best service in 2018.